Tackling the Italian emergency 2019-nCoV: nurses’ knowledge, attitudes and behaviors: What we know about the COVID-19? - Rosa, Debora; Villa, Giulia; Giannetta, Noemi; Dionisi, Sara; Togni, Serena; Bonetti, Loris; Terzoni, Stefano; Di Muzio, Marco; Di Simone, Emanuele (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: The aim was to understand the knowledge, attitudes, and behaviors of Health Care workers regarding the Novel Coronavirus 2019 cases at the start of the diffusion of the disease in Italy. Methods: Cross‐sectional survey of nurses working in Italian hospitals. Results: Most of the sample showed good knowledge and behaviors about the new virus and good attitudes. Logistic regression analysis demonstrated that predictive variables of knowledge, attitude, and behavior were: educational background, work experience years and age of nurses. Conclusions: This study is the first one in a time of a full health emergency. It would be appropriate to develop further studies to better analyze the skills implemented to tackle Novel Coronavirus 2019 disease. Novel Coronavirus 2019 pandemic has put on health personnel a considerable workload. Despite this, the Italian nursing staff has been showing excellent knowledge, attitude, and good behavior in the management of this pandemic. (www.actabiomedica.it)